Random Occupation of Multimetal Sites in Transition Metal‐Organic Frameworks for Boosting the Oxygen Evolution Reaction. Issue 14 (9th February 2022) - Yao, Yuechao; Ma, Zhongtao; Dou, Yibo; Lim, Sung Yul; Zou, Jizhao; Stamate, Eugen; Jensen, Jens Oluf; Zhang, Wenjing
Abstract: Developing robust oxygen evolution reaction (OER) electrocatalysts with excellent performance is essential for the conversion of renewable electricity to clean fuel. Herein, we present a facile concept for the synthesis of efficient high‐entropy metal‐organic frameworks (HEMOFs) as electrocatalysts in a one‐step solvothermal synthesis. This strategy allows control of the microstructure and corresponding lattice distortion by tuning the metal ion composition. As a result, the OER activity was improved by optimizing the coordination environment of the metal catalytic center. The optimized Co‐rich HEMOFs exhibited a low overpotential of 310 mV at a current density of 10 mA cm −2, better than a RuO2 catalyst tested under the same conditions. The finding of lattice distortion of the HEMOFs provides a new strategy for developing high‐performance electrocatalysts for energy conversion. Abstract : Less order, more action : Compared to single metal‐organic frameworks (MOFs), the random occupation of multi‐metal nodes in transitional MOFs builds a high‐entropy state. Furthermore, this high‐entropy‐state MOFs caused a partial crystal distortion that can break up the catalytic atom's saturated coordination environment to produce a highly active unsaturated state, optimizing the adsorption energies between oxygen intermediates and catalytic centres.